2016
DOI: 10.1177/0142723716673954
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of verb number morphemes in Czech children: Singular and plural show different relations to age and vocabulary

Abstract: Two experiments examined Czech children's comprehension of grammatical number marking in verbs. Children were presented with picture pairs involving one or multiple participants in the same action, and were asked to point to the picture described by a recorded sentence. Experiment 1 (N = 72, age 3;0-4;7) tested four types of sentences, some of which marked the number of participants on the verb only. There was a marked increase in comprehension scores with age and receptive vocabulary scores in singular, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In our first study, children also underperformed, but only with third-person singular subjects in the null subject condition, and there is no clear motive why it should be so. Numerous studies have found number (singular, plural) asymmetries (Johnson et al, 2005; Legendre et al, 2014; Pérez-Leroux, 2005; Smolík & Bláhová, 2016; Verhagen & Blom, 2014; among others). In terms of the syntactic mechanisms involved, there is no reason to expect singular to be more difficult or easier than plural: the underlying matching mechanism is the same, and so no differences are predicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our first study, children also underperformed, but only with third-person singular subjects in the null subject condition, and there is no clear motive why it should be so. Numerous studies have found number (singular, plural) asymmetries (Johnson et al, 2005; Legendre et al, 2014; Pérez-Leroux, 2005; Smolík & Bláhová, 2016; Verhagen & Blom, 2014; among others). In terms of the syntactic mechanisms involved, there is no reason to expect singular to be more difficult or easier than plural: the underlying matching mechanism is the same, and so no differences are predicted.…”
Section: Discussionmentioning
confidence: 99%
“… 5. Smolík and Bláhová (2016) further suggest that some of the problems associated with pointing may be avoided in truth value judgment tasks, something that remains for future research. …”
mentioning
confidence: 98%
“…In the current Czech linguistic environment and renewed interest in child language the main attention has been paid to pre-school age language acquisition, e.g. Smolík & Bláhová (2017);Smolík & Seidlová Málková (2014); Saicová Římalová (2013); Doleží (2014); Mertins et al (2014). It might seem that once children enter school there are not many things going on linguistically speaking.…”
Section: Discussionmentioning
confidence: 99%